Mobile Technology in Indonesian Nursing Education: Potential and Challenge - David Sulistiawan Aditya; Edy Suprayitno (University of Muhammadiyah Malang, 2021)
Introduction: Mobile technology such as smartphones and laptops have been a potential learning tool in both academic and clinical facets of nursing education. However, potentials and challenges of m-technology vary depending on individual, social, technological, and pedagogical conditions. And, studies of this issue in developing countries are lacking. Objective: This study aims to explore the potentials and challenges of m-technology integration in Indonesian nursing education. Method: 25 nursing faculties from three different nursing schools in Yogyakarta participated through an online questionnaire. 8 of them were purposely taken for semi -structured interviews. The data were presented cross-sectionally through descriptive statistics and ascertained with participants voices. Results: The findings delineated how mobile technology leveraged in both academic and clinical of nursing instructions. Three main potentials identified were to promote ubiquitous learning, build autonomous learning, and enhance technological knowledge. Technology affordances, psychological aspects, and nursing students attitude emerged as challenges in the current nursing education context. Social, individual, technological, and pedagogical aspects were discussed. Conclusion: Mobile technology is potential to mediate and provide better learning for nursing students in academic and clinical settings. However, faculties’ pedagogical knowledge and learning regulation of online learning are required to be analysed further.